Progress in the development of gelling agents for improved culturability of microorganisms - Das, Nabajit; Triparthi, Naveen; Basu, Srijoni; Bose, Chandra; Maitra, Susmit; Khurana, Sukant (Frontiers in Microbiology, 2015)
Gelling agents are required for formulating both solid and semisolid media, vital for the isolation of microorganisms. Gelatin was the first gelling agent to be discovered but it soon paved the way for agar, which has far superior material qualities. Source depletion, issues with polymerase-chain-reaction and inability to sustain extermophiles etc., necessitate the need of other gelling agents. Many new gelling agents, such as xantham gum, gellan gum, carrageenan, isubgol and guar gum have been formulated, raising the hopes for the growth of previously unculturable microorganisms. We evaluate the progress in the development of gelling agents, with the hope that our synthesis would help accelerate research in the field.